Engineering statics - Islam, M. Rashad; Al Faruque, M. Abdullah; Zoghi, Bahar; Kalevela, Sylvester (Boca Raton : CRC Press, 2021)
"Engineering statics presents the cutting-edge topics in engineering statics, focusing on practical applications knowledge, with numerous real-world examples, practice problems, and case studies throughout. It covers theory concisely and uses plain language and coverage that can be completed in a one-semester course. It also covers the related concepts required to take the Fundamentals of Engineering (FE) exam. Features: Written in plain language, with numerous realistic step-by-step examples, covers topics required to understand and prepare for the Fundamentals of Engineering (FE) exam, includes practical case studies, concise theory and numerous solved practice problems. Engineering statics is suitable for undergraduate students in civil and mechanical engineering courses, as well as those in Engineering technology and applied courses. Research ambiguities are avoided considering the interests of lower-division students. The authors believe that this text will be very helpful for students to succeed in their degree programs and professional careers"--
OCLC-licensed vendor bibliographic record.
Keywords: Statics; SCIENCE / Mechanics / Statics